2018
DOI: 10.1111/nph.14992
|View full text |Cite
|
Sign up to set email alerts
|

Medicago truncatula copper transporter 1 (MtCOPT1) delivers copper for symbiotic nitrogen fixation

Abstract: Copper is an essential nutrient for symbiotic nitrogen fixation. This element is delivered by the host plant to the nodule, where membrane copper (Cu) transporter would introduce it into the cell to synthesize cupro-proteins. COPT family members in the model legume Medicago truncatula were identified and their expression determined. Yeast complementation assays, confocal microscopy and phenotypical characterization of a Tnt1 insertional mutant line were carried out in the nodule-specific M. truncatula COPT fam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 91 publications
1
41
0
Order By: Relevance
“…Our results also indicate that there must be some systemic signal indicating that zinc is limiting within the cell and that more of this element is required, which would explain why nodule zinc concentrations increase in the mtzip6 RNAi nodules rather than remaining equal or even lower. Similar observations have been made when studying two M. truncatula mutants in nodule‐specific molybdate and copper transporters (Tejada‐Jiménez et al, ; Senovilla et al, ).…”
Section: Discussionsupporting
confidence: 75%
“…Our results also indicate that there must be some systemic signal indicating that zinc is limiting within the cell and that more of this element is required, which would explain why nodule zinc concentrations increase in the mtzip6 RNAi nodules rather than remaining equal or even lower. Similar observations have been made when studying two M. truncatula mutants in nodule‐specific molybdate and copper transporters (Tejada‐Jiménez et al, ; Senovilla et al, ).…”
Section: Discussionsupporting
confidence: 75%
“…The mot1.3‐1 phenotype is molybdenum‐dependent, as molybdate fortification of the nutritive solution resulted in wild‐type‐looking mot1.3‐1 plants, in apparent contradiction to the higher levels of molybdenum detected in mot1.3‐1 nodules. This accumulation pattern has also been observed when studying a nodule‐specific plasma membrane copper transporter and a nodule‐induced zinc transporter (Abreu et al ., ; Senovilla et al ., ). One possible explanation is the existence of a signal indicating intracellular metal deficiency that would trigger more metal being transported to the nodule.…”
Section: Discussionmentioning
confidence: 97%
“…Metallic micronutrient delivery to nodules is essential for symbiotic nitrogen fixation, as they are cofactors in many of the involved enzymes (Brear et al, 2013;González-Guerrero et al, 2014). In recent years, studies have shown how metals are exported to the apoplast in the infection/differentiation zone of M. truncatula nodules (Rodríguez-Haas et al, 2013), and transmembrane transporters introduce metals into rhizobiainfected cells (Tejada-Jiménez et al, 2015;Abreu et al, 2017;Tejada-Jiménez et al, 2017;Senovilla et al, 2018), or deliver iron to the bacteroids (Escudero et al, 2019b). In this transport, citrate participates in maintaining iron solubility in the apoplast, and as the preferred iron source for bacteroids (Moreau et al, 1995;LeVier et al, 1996;Kryvoruchko et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This includes not only nitrogenase (Rubio and Ludden, 2005), but also nicotinamide adenine dinucleotide phosphate (NADPH)-oxidases that participate in nodule signaling (Montiel et al, 2016), leghemoglobin that maintains nodule O 2 homeostasis (Appleby, 1984), high-affinity cytochrome oxidases providing energy to the bacteroids (Preisig et al, 1996), as well as many enzymes involved in free radical control (Dalton et al, 1998;Santos et al, 2000;Rubio et al, 2007). Consequently, deficiencies in the uptake of these nutrients or alterations in the metal delivery pathways lead to defects in nodulation and/or nitrogen fixation (Tang et al, 1991;O'Hara, 2001;Senovilla et al, 2018;Gil-Díez et al, 2019).…”
Section: Introductionmentioning
confidence: 99%